2022
DOI: 10.1177/07334648211073607
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Stay-At-Home Restrictions on Falls in One Community of High-Risk Older Adults

Abstract: Aim: To examine the relationship between falls among high-risk older adults at one Program of All-Inclusive Care for the Elderly (PACE) and the COVID-19 closure of its Day Health Center (DHC), which provides participants with social and rehabilitative services and contributes to their weekly physical activity. Methods: Self-reported falls during the 3 months before the DHC’s closure (“pre–COVID-19”) were compared in number and in character to falls during its closure (“COVID-19”). Results: One thirty five part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
(17 reference statements)
0
9
1
Order By: Relevance
“…In the context of the ongoing COVID-19 pandemic, older adults are at risk of experiencing a chronic array of stressors that could accelerate frailty, including malnutrition, delaying routine medical care, drastic reduction in meaningful social interaction, and limited opportunity for exercise ( Boreskie et al, 2020 ; Czeisler et al, 2020 ; Steinman et al, 2020 ). The long-term consequences of COVID-19—related decline in physical activity—such as deconditioning and falls—has been raised as an area of particular concern ( McIntyre et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the ongoing COVID-19 pandemic, older adults are at risk of experiencing a chronic array of stressors that could accelerate frailty, including malnutrition, delaying routine medical care, drastic reduction in meaningful social interaction, and limited opportunity for exercise ( Boreskie et al, 2020 ; Czeisler et al, 2020 ; Steinman et al, 2020 ). The long-term consequences of COVID-19—related decline in physical activity—such as deconditioning and falls—has been raised as an area of particular concern ( McIntyre et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Results of presentations with falls to the ED are diverse reporting higher [12] or lower numbers during the pandemic period [13][14][15][16]. In our study, we showed that the number of geriatric fall presentations to ED, comorbidity burden, consultations, and LOS at the ED in those patients was lower, but direct costs were higher in the pandemic period than pre-pandemic period.…”
Section: Discussionmentioning
confidence: 56%
“…The risk of falls was predicted to increase in older individuals because of the negative effects of the COVID-19 pandemic [7,10,24,25]. However, presentations with falls have decreased during the pandemic period in the studies carried out in EDs and other settings [13][14][15][16][27][28][29]. It is considered that approximately half of all falls occur outside the home [30], and in Turkey, there were strict stay-at-home restrictions for older adults at the beginning of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, there were increased fears associated with falling and loss of mobility 10 13. Longitudinal studies have reported that while the rates of falls were initially lower compared with the prepandemic era,14 15 falls and orthopaedic injuries subsequently increased when restrictions were lifted,16 17 potentially reflecting the deconditioning and impaired balance that accrued with sedentarism 10…”
Section: Introductionmentioning
confidence: 99%